Analisis Pengaruh Customer Experience dan Promosi Penjualan Terhadap Kepuasan Pelanggan dan Minat Beli Ulang Pada Starbucks Coffee di Pontianak : Perspektif B2C - ERIK JUNIWATI HERIYADI (Universitas Tanjungpura, 2021)
This research aims to know the influence of customer experience, sales promotion, customer satisfaction and re-purchase interest on Starbucks Coffee.The research was conducted in Pontianak City, using a sample size of 100 people.The sampling technique used is Non Probability Sampling by sampling method is Purposive Sampling.Data obtained by conducting online questionnaire and data analysis method with SEM-PLS using software WarpPLS 6.0 data analysis techniques used in the form of validity test, reliability test, model goodness test, T test and Sobel test.The results of this research show that the customer experience and sales promotion have positive and significant effect on customer satisfaction with a coefficient of determination value of 61%.Customer experience, sales promotions and customer satisfaction have a positive and significant effect on the interest of repurchase with a coefficient of determination of 54.2%.Customer satisfaction is capable of positively and significantly the impact of customer experience on repurchase interest with a P-value value of 0.002. Customer satisfaction does not efficiently and positively and significantly influence the sales promotion to a repurchase interest with a P-value of 0.127.Starbucks Coffee is expected to provide and improve the better service to its customers so as to create customer experience that is expected by the customer and provide a sales promotion that is in accordance with the expectations of consumers so as to have an impact on the interest in buying consumers at Starbucks Coffee in Pontianak.